Experimental validation of analytical models for liquid film breakup on rotating substrates. (20th July 2019) - Line, Håkon; Steiner, Helfried; Brenn, Günter
Highlights: Several models for predicting minimum stable film heights have been validated. For centrifugal spreading, wetting equilibrium yields film of constant surface area. Equilibrium given by balance of inertial, viscous and capillary contributions. Blended length scale approach required for a generally valid wetting model. Abstract: Many models for predicting the breakup of liquid films spreading over solid substrates have been proposed over the years, each taking a different approach to modelling the minimum stable film height. There is not a lot of reliable experimental data in the literature for validating these models, however, as previous measurement campaigns have generally relied on the relatively weak gravitational force as a wetting driver, making the results sensitive to minor flow disturbances and flaws in the substrate. The present work considers experimentally the breakup of films spreading radially over rapidly rotating substrates, where the much stronger centrifugal force takes the place of gravity. An empirical correlation has been derived from the presently generated data and compared with analytical predictions. The predictions of the analytical wetting models, appropriately modified, were additionally validated against the observed radial breakup locations. The models which considered an equilibrium of surface tension and inertia were found to give the best overall agreement with the data. However, it was also shown that the retarding effect of viscous shear needs to be taken into account in the modelling and that a blended approach incorporating both inertial and viscous length scales is necessary in order to obtain a generally valid model.